Character strengths predict resilience over and above positive affect, self-efficacy, optimism, social support, self-esteem, and life satisfaction. Issue 2 (4th March 2017) - Martínez-Martí, María Luisa; Ruch, Willibald
Abstract: The incremental value of character strengths in the prediction of resilience, after the effects of other well-known resilience-related factors (i.e. positive affect, self-efficacy, optimism, social support, self-esteem, life satisfaction) and sociodemographic variables are accounted for, is examined. Using a cross-sectional design, participants ( N = 363 adults) completed online measures of character strengths, resilience, and resilience-related factors. A principal component analysis of character strengths was conducted and five factors were extracted, which could be interpreted as emotional, interpersonal, intellectual, restraint, and theological strengths. All strengths factors, except theological strengths, yielded significant positive correlations with resilience. A hierarchical regression showed that strengths predicted an additional 3% of the variance in resilience over and above sociodemographic variables, positive affect, self-efficacy, optimism, social support, self-esteem, and life satisfaction. Emotional strengths and strengths of restraint were significant positive predictors. Implications, limitations, and future research are discussed.